Low Cost Travel Packages Drive Domestic Tourism Growth in Uzbekistan - Khusen Ibargimov; Suyunova Feruza; Sanakulova Aziza; Nurmuhammadova Sabina (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Domestic tourism is increasingly recognized as a vital contributor to national economies, particularly in developing countries like Uzbekistan. Specific Background: Despite policy initiatives promoting internal travel, limited data exists on how affordable travel options shape domestic tourism behavior. Knowledge Gap: Little is known about the perceived accessibility and value of low-cost travel packages among Uzbekistani residents. Aims: This study aims to evaluate perceptions of low-cost travel packages and identify key factors associated with their appeal to domestic tourists. Results: Based on a mixed-methods approach involving 37 online survey respondents and statistical analysis using SPSS, the study finds that perceptions of value-for-money are significantly shaped by travel frequency and the quality of customer service. Novelty: The research uniquely combines quantitative and qualitative evidence to illuminate how localized, budget-friendly travel options influence domestic tourism patterns in a Central Asian context. Implications: The findings suggest that to stimulate domestic tourism growth, stakeholders should prioritize promotional strategies, raise public awareness, and develop tailored, affordable travel packages for local residents. While the study's small sample limits generalizability, it provides a foundational basis for future research involving broader populations to validate and expand upon these insights. Highlights: Value perception is shaped by travel frequency and service quality. Custom low-cost packages can boost local tourism participation. Small sample limits generalizability; broader studies are needed. Keywords : Domestic Tourism, Uzbekistan, Customer Satisfaction, Travel Packages, Statistical Analysis